ASSISTANCE OF TOURISM LEARNING MODELS TO INCREASE CHILDREN’S LEARNING ENTHUSIASM OF LERENG BAYANGKAKI - Linda Ayu Karisma; Safana Reih Tazkiya; Arif Rahman Hakim (IAIN AMBON, 2021)
ABSTRACTMlokolegi Hamlet, Temon Village, is a village located in Sawoo District, Ponorogo Regency, East Java, Indonesia. Temon Village has various natural resources (SDA) that have the potential to be developed. In contrast to the condition of existing natural resources, the quality of human resources (Human Resources) is still in the development stage, both in understanding the knowledge of environmental potential and skills in facing competition. Limitations in the learning process in Temon Village are an inhibiting factor in improving the quality of education. Based on the results of observations using the ABCD (Asset Based Community Development) method, the potential for enthusiasm for learning for the children of the Bayangkaki slopes is a provision to carry out mentoring activities for the learning model of field trips. This is supported by the soothing natural conditions of the Bayangkaki slopes as a location for learning activities. In the midst of the mentoring process that has been carried out, the enthusiasm of the sons and daughters of the Bayangkaki slopes has increased. This statement is evidenced by the increasing number of activity participants in each meeting as well as arrivals that are earlier than the predetermined schedule. The results of the implementation of the study tour show that overall the sons and daughters of the Bayangkaki slopes through nature school activities have increased knowledge and are more comfortable in the learning process. The existence of assistance with the field trip method is the right and effective strategy in achieving learning objectives as an effort to improve the quality of human resources in Mlokolegi Hamlet, Temon Village.Key Word: Enthusiasm to learn, Human Resource, Field trip Learning, Asset Based Community Development ABSTRAKDusun Mlokolegi Desa Temon merupakan desa yang terletak di Kecamatan Sawoo Kabupaten Ponorogo Jawa Timur Indonesia. Desa Temon memiliki SDA (Sumber Daya Alam) beragam yang berpotensi untuk dikembangkan. Berbeda hal nya dengan kondisi SDA yang ada, kualitas SDM (Sumber Daya Manusia) masih dalam taraf perkembangan baik dalam memahami pengetahuan potensi lingkungan maupun ketrampilan menghadapi persaingan. Keterbatasan dalam proses pembelajaran di Desa Temon menjadi faktor penghambat peningkatan kualitas pendidikan. Berdasarkan hasil observasi menggunakan metode ABCD (Asset Based Community Development), adanya potensi antusiasme belajar putra putri lereng Bayangkaki menjadi bekal untuk melaksanakan kegiatan pendampingan model pembelajaran karya wisata. Hal ini didukung dengan kondisi alam lereng Bayangkaki yang menenangkan sebagai lokasi kegiatan pembelajaran. Ditengah proses pelaksanaan pendampingan yang telah di laksanakan, antusiasme putra putri lereng Bayangkaki mengalami peningkatan. Pernyataan tersebut dibuktikan dengan bertambahnya jumlah peserta kegiatan dalam setiap pertemuan serta kedatangan yang lebih awal dari jadwal yang telah ditentukan. Hasil pelaksanaan pembelajaran karya wisata menunjukkan bahwa secara keseluruhan putra putri lereng Bayangkaki melalui kegiatan sekolah alam mengalami peningkatan pengetahuan dan semakin nyaman dalam proses pembelajaran. Adanya pendampingan dengan metode karya wisata menjadi strategi yang tepat dan efektif dalam mencapai tujuan pembelajaran sebagai upaya peningkatan kualitas SDM di Dusun Mlokolegi Desa Temon.Kata kunci: Antusiasme belajar, Sumber Daya Manusia, Pembelajaran Karyawisata, Asset Based Community Development